Application of small‐bore pigtail catheter to improve pleural drainage after single‐incision thoracoscopic lobectomy for lung cancer. Issue 1 (11th December 2019) - Yang, Zhenhua; Hu, Tianjun; Shen, Haibo; Huang, Hongbo
Abstract: Background: In order to overcome the problems associated with the drainage of single‐incision thoracoscopic surgery, we investigated the efficiency of applying an 8‐Fr pigtail catheter in addition to the conventional 26‐Fr chest tube. Methods: This prospective study includes 88 consecutive patients who underwent single‐incision thoracoscopic lobectomy between July 2017 and March 2018. Patients were treated either with (smaller pigtail group) or without (larger drain group) 8‐Fr pigtail catheter in addition to conventional 26‐Fr chest tube. Post‐operative recovery was assessed by analysing the post‐operative drainage volume on the first 2 days, the duration (days) of drainage, re‐intubation after 2 weeks, air leak time, length of stay, subcutaneous emphysema, pleural effusion after 2 weeks and pain score. Results: The patients in the pigtail tube group had a significantly shorter drainage time and higher drainage volume on the first 2 days than those in the larger drain group. The percentage of patients that developed pleural effusion after 2 weeks was 4.54% in the smaller pigtail group and 25% in the larger drain group ( P = 0.007). The pain score in the smaller pigtail tube group decreased significantly on the third day after surgery compared with larger drain group ( P < 0.001). There were no significant differences between the two groups in the air leak time, subcutaneous emphysema, wound healing and pain score on the first day. Conclusion: Application of 8‐Fr pigtail catheter after single‐incision thoracoscopic lobectomy for primary lung cancer can accelerate the post‐operative recovery of patients. Abstract : Pleural effusion after 2 weeks was decreased and the pain score decreased on the third day after surgery. Effective drainage after single‐incision thoracoscopic lobectomy can accelerate the post‐operative recovery of patients with lung cancer.